1998
DOI: 10.1007/s005860050092
|View full text |Cite
|
Sign up to set email alerts
|

Self reported health status and magnetic resonance imaging findings in patients with low back pain

Abstract: The authors present a prospective study of quality of life and MRI findings in patients with low back pain (LBP). Disc herniation and nerve root compression contribute to LBP and poor quality of life. However, significant proportions of asymptomatic subjects have disc herniation and neural compromise. Little is known about the influence of disc abnormalities and neural compression on quality of life in symptomatic patients. The purpose of this study was to assess the relationship between the extent of disc ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 29 publications
3
18
0
3
Order By: Relevance
“…Clinically, mechanical compression of the lumbar spinal nerve roots, either by disc prolapse or spinal stenosis, is a common mechanism of painful lumbar radiculopathy [7,27,35]. Though the symptoms and physical sign are clear in clinic, but the pathophysiology of the back pain and radiculopathy associated with lumbar stenosis and lumbar disc herniations is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, mechanical compression of the lumbar spinal nerve roots, either by disc prolapse or spinal stenosis, is a common mechanism of painful lumbar radiculopathy [7,27,35]. Though the symptoms and physical sign are clear in clinic, but the pathophysiology of the back pain and radiculopathy associated with lumbar stenosis and lumbar disc herniations is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Painful lumbar radiculopathy (LR) commonly results from mechanical compression of lumbar nerve roots, either by disc prolapse or spinal stenosis [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that patients complaining of numbness have a higher probability of medullary signal alteration on MR imaging [25]. The selection of patients with higher scores for sleeping and numbness would probably decrease the number of negative MR examinations [8].…”
Section: Discussionmentioning
confidence: 99%